CMEI – Centro Municipal de Educação Infantil Integral Estendido: uma creche de tempo diário ampliado em amparo aos trabalhadores do Centro de Manaus - Magalhaes, Ana Karina Pereira de (Brasil, 2025)
The present work aims to propose a public Early Childhood Education Center in Manaus Downtown, which has as its differential the alteration and extension of opening hours, in order to correspond to the particularities of the workday carried out by parents and guardians, in addition to expanding access to the rest of the community and support the lack of education units in the region. As well as collaborating with the Municipal Education Plan, showing the significance of introducing children to education at an early age and promoting the importance of architecture in schools, as a contributing element in children's pedagogical development.